Analysis of Implementation of National Education Standards (Case Study at SMAS BS Miftahul Ulum Terisi) - Syaiful Mujab; Muchtarom Muchtarom; Mohammad Hasan (Universitas Muhammadiyah Enrekang, 2023)
Improving the quality of education through the implementation of national education standards is the background of this research. The purpose of this research is to find out and analyze the Implementation of National Education Standards. This research is a qualitative research with a case study approach. This research case study was carried out at SMAS BS Miftahul Ulum Terisi, Indramayu Regency. This research was conducted in the odd semester of the 2023/2024 Academic Year. Informants in this study were school principals, vice principals and teachers of SMAS BS Miftahul Ulum Terisi. Collection techniques used are observations, interviews, and documentation. The data analysis technique used is to record the results of field observations, collect and select and sort data, make patterns of relationships and findings. The results of this study indicate that 1) SMAS BS Miftahul Ulum Terisi has implemented eight national education standards well, but each of them has several challenges that need to be faced, 2) There are several factors that affect the implementation of the SNP, namely the availability of resources, government policies, improving the school's image , environmental conditions, the role of stakeholders and school culture, and 3) The impacts of implementing the SNP are improving the quality of education, increasing student motivation, improving school image and increasing student employment opportunities.